Off-label use of tumescent local anaesthesia in endovascular and surgical techniques - Frings, N.; Glowacki, P.; Greiner, A.; Rass, K. (Phlebologie, 2016)
Tumescent local anaesthesia (TLA)has increasingly established itself as the anaesthesia method for operations on varicose veins and has become the standard method in the case of endovascular techniques. However, Off-label use occurs due to the reduced concentration of the local anaesthetic, the incorporation of additives together with a high quantity of LA which exceed the manufacturer’s recommended maximum dosage. In spite of a lack of significant complications arising from the approved use of the TLA and unambiguous positive evaluations of this anaesthesia method by international medical professional associations, the operating phlebologist should inform the patient of this Offlabel use both in the case of operative procedures and endovascular techniques in order to avoid any legal problems.Das Anästhesieverfahren der Tumeszenzlokalanästhesie (TLA) hat sich bei Varizenoperationen zunehmend etabliert und stellt bei endovasalen Techniken das Standardverfahren dar. Es handelt sich jedoch um einen Off-Label-Use, wegen der verminderten Konzentration des Lokalanästhetikums, Beimischung von Zusatzstoffen sowie hoher LA Menge, welche die vom Hersteller empfohlenen Maximaldosen überschreiten. Trotz fehlender gravierender Komplikationen bei bestimmungsmäßigem Einsatz der TLA sowie eindeutig positiven Bewertungen dieser Anästhesietechnik durch internationale medizinische Fachgesellschaften sollte der Operateur darum den Patienten sowohl bei einer Operation als auch bei endovasalen Techniken über diesen Off-Label-Use aufklären, um juristische Probleme zu vermeiden.
Keywords: Tumescent local anaesthesia; Off-label use; varicose vein surgery; endovascular occlusion of varicose veins